Coronavirus infection in India: A dental surgeon's perspective - Malvika Singh (Apollo Medicine)
Of what was identified by the Chinese government in China's Wuhan district on January 7, 2020, and declared as a pandemic by the World Health Organization on March 11, 2020, severe acute respiratory syndrome-coronavirus 2 (CoV-2), most commonly known as 2019 novel CoV infection, has become a major challenge not only for India but also for the whole world. As on April 26, 2020, this viral infection has been recognized in over 200 countries, claiming 169,006 lives and infecting 2,471,136 people worldwide. The infection travels via respiratory droplets and clinical signs, and the symptoms include dry cough, fatigue, coughing sputum, and shortness of breath. Dental clinics are most susceptible to such infection since there is continuous production of aerosol making dental professionals highly vulnerable to the same and since there has not been a definitive pharmaceutical treatment for this infection, the whole situation makes it even more scary. This article is an attempt to throw light on CoV infection and enumerates certain preventive measures that can be taken in dental clinics while treating emergency cases along with preventing the spread to this deadly viral infection.